Isolated Hallucination as a Consequence of SARS-CoV-2 Infection in a 10-year-old Child. (January 2022) - Pleszkó, Apollónia; Pauleczki, Annamária; Óvári, Ignác; Óvári, József; Hauser, Péter
Spectrum of childhood symptoms caused by SARS-CoV-2 (severe acute respiratory syndrome-2) infection is widening. In contrast to adulthood, where psychiatric disorders caused by SARS-CoV-2 infection are widely known, recognition of such cases in childhood is still quite rare. Recurrent isolated hallucinations caused by SARS-CoV-2 infection in the absence of other neuropsychiatric symptoms are not yet described in this age group. SARS-CoV-2 infection was confirmed as a cause of recurrent isolated hallucinations in a 10-year-old child, which have most likely disappeared as a consequence of corticosteroid treatment. SARS-CoV-2 infection should also be considered in case of an otherwise healthy child with emerging psychiatric symptoms, which may be cured by corticosteroids.